Comparison of Effects Antibiotics and Natural Honey and Extracts of Plants on Escherichia coli Growth Isolated from Different Pathogenic Cases (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2019)
This study included four aspects:Collection of 200 samples of patients with four different pathogenic cases: Burns infections, Wound infections, Urinary Tract Infections & diarrhea , for period ( September 2016 – March2017) . 403 bacterial isolates were got. Gram negative bacteria represented  329  isolates (48.9%  E.coli ). The percentages of E.coli  isolates  are different depending on isolation sources and the Urinary Tract Infections have the highest (72.2%).Antibiotic Susceptibility test was performed for 10  antibiotics, all isolates of  E.coli  showed perfect resistance against  Penicillins & Cephalosporins while they have high sensitivity to Nitrofurantion . The other  6 antibiotics have different effects depending on the isolation sources.Natural Honey has potential high ability for  E.coli  growth inhibiting without any influence with isolation sources , MIC of Ntural Honey is  15%.The inhibition activity was tested for Ethanol (95%) Extracts of four Medicinal plants : Allium sativum , Paganum harmala , Nigella sativum & Myrtus communs . All of these extracts have high inhibitory effect on  E.coli  isolates without any influence of the isolation sources. Allium sativum extract has the highest effect with inhibition zone diameters (20.1-32.0) mm.